1998
DOI: 10.7589/0090-3558-34.4.764
|View full text |Cite
|
Sign up to set email alerts
|

Gray Fox Response to Baits and Attractants for Oral Rabies Vaccination

Abstract: Rabies is a widespread zoonosis that recently reached epidemic proportions in gray foxes (Urocyon cinereoargenteus) in central Texas. The objectives of this study were to determine bait and attractant preferences among captive gray foxes, to determine the behavioral responses of gray foxes to selected bait-attractant combinations, and to evaluate baits as a delivery mechanism of oral rabies vaccines. Trials were conducted to determine bait preferences of captive gray foxes to selected baits and attractants. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A significant aspect of recent ORV development has been efforts aimed at evaluating different bait types, bait attractants, and delivery methods in order to maximize vaccine bait discovery and ingestion by vector species (Linhart et al, 1997b;Farry et al, 1998aFarry et al, , 1998bSteelman et al, 1998Steelman et al, , 2000. In the United States, the extruded fish meal polymer bait for raccoons (Procyon lotor) and coyotes (Bait-Tek, Inc., Beaumont, Texas, USA) has evolved as the current bait of choice for both species (Hanlon et al, 1989;Fearneyhough et al, 1998;Olson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A significant aspect of recent ORV development has been efforts aimed at evaluating different bait types, bait attractants, and delivery methods in order to maximize vaccine bait discovery and ingestion by vector species (Linhart et al, 1997b;Farry et al, 1998aFarry et al, , 1998bSteelman et al, 1998Steelman et al, , 2000. In the United States, the extruded fish meal polymer bait for raccoons (Procyon lotor) and coyotes (Bait-Tek, Inc., Beaumont, Texas, USA) has evolved as the current bait of choice for both species (Hanlon et al, 1989;Fearneyhough et al, 1998;Olson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the polymer-based baits would be limited to winter use in central Texas; whereas the marshmallow wax cakes could be used throughout the year. Lastly, gray foxes exhibit chewing behaviors of the wax cake baits that would facilitate ingesting an oral vaccine (Steelman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative that a bait and baiting strategy be developed for each target species. Steelman et al (1998) found that gray foxes from central Texas exhibited preferences for marshmallow wax cakes and dog food-based polymer baits with a lard interior and granulated sugar exterior; however, these preferences were determined using captive animals. All baits must be field tested to verify that captivity did not alter typical behavior of gray foxes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations